2003
DOI: 10.1016/s0735-1097(03)00184-0
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and cardiovascular disease

Abstract: Obstructive sleep apnea (OSA) is a common disorder associated with an increased risk of cardiovascular disease and stroke. As it is strongly associated with known cardiovascular risk factors, including obesity, insulin resistance, and dyslipidemia, OSA is an independent risk factor for hypertension and has also been implicated in the pathogenesis of congestive cardiac failure, pulmonary hypertension, arrhythmias, and atherosclerosis. Obesity is strongly linked to an increased risk of OSA, and weight loss can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
232
1
28

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(270 citation statements)
references
References 85 publications
4
232
1
28
Order By: Relevance
“…3 Previous studies have suggested that OSAS acts as an independent risk factor and leads to hypertension, heart disease, and stroke through the mechanisms described above. [4][5][6] OSAS can have a similar effect on the eye. According to some reports, the prevalence of primary open-angle glaucoma is increased in patients with OSAS.…”
Section: Introductionmentioning
confidence: 98%
“…3 Previous studies have suggested that OSAS acts as an independent risk factor and leads to hypertension, heart disease, and stroke through the mechanisms described above. [4][5][6] OSAS can have a similar effect on the eye. According to some reports, the prevalence of primary open-angle glaucoma is increased in patients with OSAS.…”
Section: Introductionmentioning
confidence: 98%
“…81,82 The association between obstructive sleep apnea and atherosclerosis appears to be primarily mediated via coexisting factors including central obesity, insulin resistance and dyslipidaemia. 83 However, obstructive sleep apnea directly influences BP and lipid loading of macrophages. 83,84 The mechanisms that link hypertension with atherosclerosis are not very well understood, although the physical stress on the vessel wall appears to be the primary factor involved.…”
Section: Mechanisms Linking Obesity and Atherosclerosismentioning
confidence: 99%
“…83 However, obstructive sleep apnea directly influences BP and lipid loading of macrophages. 83,84 The mechanisms that link hypertension with atherosclerosis are not very well understood, although the physical stress on the vessel wall appears to be the primary factor involved. 85 Obesity is also associated with increased levels of inflammation and oxidative stress, which are recognised as important factors influencing atherosclerosis.…”
Section: Mechanisms Linking Obesity and Atherosclerosismentioning
confidence: 99%
“…The prevalence of OSA among obese patients has been reported, and substantial improvement was achieved by weight reduction. 2 Regarding the pathophysiology of OSA, an anatomically small pharyngeal airway is a prerequisite factor leading to OSA. This smaller airway size always worsens with increasing body fat and obesity.…”
mentioning
confidence: 99%
“…2 Although co-founding variables made it difficult to directly link OSA and left ventricular hypertrophy, a close relationship between these two pathological conditions could dramatically and negatively impact patients' prognoses; therefore, molecular mechanisms that could establish a causal relationship between OSA and left ventricular hypertrophy should be more extensively studied. In this issue of Hypertension Research, Inamoto et al 10 examined the effects of statin therapy on intermittent hypoxia-induced left ventricular remodeling in mice, a known model for OSA.…”
mentioning
confidence: 99%